Extruded thermoplastic elastomers styrene-butadiene-styrene/carbon nanotubes composites for strain sensor applications - Costa, Pedro (2014)
Tri-block copolymer styrene–butadiene–styrene (SBS) composites with different butadiene/styrene ratios and multi-walled carbon nanotubes (MWCNTs) can be used for the development of electro-mechanical sensors for large strains applications. Extruded CNT/SBS composites show percolation thresholds around 5 wt%, electro-mechanical properties with high sensibility at larger strain and the gauge factor reach values up to 30 at strains of 20%. The butadiene/styrene ratio has influence in the mechanical and electro-mechanical properties. In one hand, the increase of the styrene content in copolymer increasing initial mechanical modulus, on the other hand, the increase of the butadiene content leads to larger maximum deformations and higher electro-mechanical sensibility for strains up to 20%. Further, applied initial pre-stress increases the electro-mechanical sensibility of the composites.